\(I=\int e^xcosxdx\)
Đặt \(\left\{{}\begin{matrix}u=e^x\\dv=cosxdx\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}du=e^xdx\\v=sinx\end{matrix}\right.\)
\(\Rightarrow I=e^xsinx-\int e^xsinxdx\)
Xét \(J=\int e^xsinxdx\Rightarrow\left\{{}\begin{matrix}u=e^x\\dv=sinxdx\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}du=e^x\\v=-cosx\end{matrix}\right.\)
\(\Rightarrow J=-e^xcosx+\int e^xcosxdx=-e^xcosx+C\)
\(\Rightarrow I=e^xsinx-\left(-e^xcosx+I\right)=e^x\left(sinx+cosx\right)-I\)
\(\Rightarrow2I=e^x\left(sinx+cosx\right)\Rightarrow I=\left(\frac{1}{2}cosx+\frac{1}{2}sinx\right)e^x\)
Hoặc đơn giản là đạo hàm F(x) và đồng nhất hệ số với f(x) là xong